Physical activity, osteoporosis, and fracture risk : long-term associations in a general population - Morseth, Bente (University of Tromsø, 2011)
The papers of this thesis are not available in Munin: 1. Morseth B, Jørgensen L, Emaus N, Jacobsen BK, Wilsgaard T.: 'Tracking of leisure time physical activity during 28 yr in adults: The Tromsø Study', Medicine & Science in sports & exercise (2011) 43(7):1229-1234. Available at http://dx.doi.org/10.1249/MSS.0b013e3182084562 2. Morseth B, Emaus N, Wilsgaard T, Jacobsen BK, Jørgensen L.: 'Leisure time physical activity in adulthood is positively associated with bone mineral density 22 years later. The Tromsø study', European Journal of Epidemiology (2010) 25:325–331. Available at http://dx.doi.org/10.1007/s10654-010-9450-8 3. Morseth B, Ahmed LA, Bjørnerem Å, Emaus N, Jacobsen BK, Joakimsen R, Størmer J, Wilsgaard T, Jørgensen L.: 'Leisure time physical activity and risk of non-vertebral fracture in women and men aged 55 years and older: The Tromsø Study' (submitted paper) Osteoporosis and related fractures are a major health problem among elderly people, and Norway has reportedly one of the highest fracture rates in the world. Many factors contribute to osteoporosis and fractures. One highly relevant protective factor is physical activity, which is a major mechanical determinant of the properties of the skeleton. Physical activity may postpone the age-related bone loss and decrease the risk of falling, and thereby reduce the risk of osteoporotic fractures. Because osteoporosis and fractures primarily occur in the elderly, it is of interest to observe the long-term benefits of physical activity. The Tromsø Study, which is a population study with recurrent surveys, provides an excellent opportunity to follow people throughout adulthood into older age. Thus, the aim of this thesis was to examine the long-term associations between physical activity and outcomes such as bone mineral density (BMD) (paper II) and risk of non-vertebral fracture (paper III) in adults. Moreover, to form a basis for these associations, the stability (i.e. tracking) of physical activity habits over three decades was investigated ...